The impact of 3-tesla breast MRI on the choice of the surgical plan in patients with multiple ipsilateral breast cancer - Bustan Mohamed Anwer; AlaaEldine AbdelHamid Mostafa; Eman ElBakoury; M. A. Elhussini; Hebatallah H. M. Hassan (The Egyptian Journal of Radiology and Nuclear Medicine)
Abstract Background For decades, oncologists recommended mastectomy as the primary treatment procedure in multiple ipsilateral breast cancer (MIBC). Recently, breast conservative surgery (BCS) has been on the rise and has become widely accepted as a less salvage procedure and of better cosmetic outcome. An ongoing dilemma has been posing a challenge between clinicians and radiologists about the optimal preoperative imaging modality for MIBC. This study aimed to assess the added value of dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) over sono-mammography (SM) in the management of MIBC and its influence on the surgical outcome. Results The study included 50 patients with suspected or proven MIBC. They were divided into two groups: group A (34/50) was managed by primary surgery, while group B (16/50) was a candidate for neoadjuvant chemotherapy followed by surgery. They all underwent SM followed by dynamic contrast-enhanced MRI and results were correlated with postoperative pathological results. In group A, DCE-MRI showed additional disease over combined SM in 27/34 (67%) in the form of multifocal, multicentric cancer and/or suspicious non-mass enhancement. DCE-MRI showed a higher correlation coefficient (r = 0.97, p < 0.001) compared to SM (r = 0.58, p = 0.001), higher sensitivity, positive predictive value, and accuracy (96.3%, 92.8%, 91%) compared to SM (74%, 90.9%, 73.5%) in assessing MIBC. Both modalities showed equivalent specificity (71.4%). In group B, MRI showed additional disease in 1/16 (6%). Both DCE-MRI and SM showed significant correlation (p < 0.001) with high correlation coefficients (r = 0.99) and (r = 0.92), respectively. In both groups, MRI results were concordant with the final surgical decision in 47/50 cases (94%), while US results were concordant with the surgical decision in 42/50 (84%). Conclusion MRI is superior to SM in assessment of MIBC and in tailoring the treatment of choice by avoiding unnecessary mastectomies or BCS with positive margins.